Robotic-assisted Versus Video-assisted Thoracoscopic Lobectomy: Short-term Results of a Randomized Clinical Trial (RVlob Trial). Issue 2 (30th April 2021) - Jin, Runsen; Zheng, Yuyan; Yuan, Ye; Han, Dingpei; Cao, Yuqin; Zhang, Yajie; Li, Chengqiang; Xiang, Jie; Zhang, Zhengyuan; Niu, Zhenyi; Lerut, Toni; Lin, Jules; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To determine whether RAL affects perioperative outcomes and long-term efficacy in NSCLC patients, compared with traditional VAL. Summary of Background Data: RAL is a promising treatment for NSCLC. However, its efficacy has not been fully evaluated. Methods: A single-center, open-labeled prospective randomized clinical trial was launched in May 2017 to compare the efficacy of RAL and VAL. By May 2020, 320 patients were enrolled. The perioperative results of RAL and VAL were compared. Results: The 320 enrolled patients were randomly assigned to the RAL group (n = 157) and the VAL group (n = 163). Perioperative outcomes were comparable between the 2 groups, including the length of hospital stay ( P = 0.76) and the rate of postoperative complications ( P = 0.45). No perioperative mortality occurred in either group. The total amount of chest tube drainage 830 mL [interquartile range (IQR), 550–1130 mL] vs 685 mL [IQR, 367.5–1160 mL], P = 0.007 and hospitalization costs [12821 (IQR, 12145–13924) vs 8009 (IQR, 7014–9003), P < 0.001] were significantly higher in the RAL group. RAL group had a significantly higher number of LNs harvested [11 (IQR, 8–15) vs 10 (IQR, 8–13), P = 0.02], higher number of N1 LNs [6 (IQR, 4–8) vs 5 (IQR, 3–7), P = 0.005], and more LN stations examined [6 (IQR, 5–7) vs 5 (IQR, 4–6), P < 0.001]. Conclusions: Both RAL and VAL are safe and feasible for the treatment of NSCLC. RAL achieved similar perioperative outcomes, together with higher LN yield. Further follow-up investigations are required to evaluate the long-term efficacy of RAL. (ClinicalTrials.gov identifier: NCT03134534)